EXPLORING EXPERIENTIAL LEARNING PRACTICES TO IMPROVE STUDENTS’ UNDERSTANDING: Received: 12th July 2021; Revised: 08th March 2022, 09th March 2022; Accepted: 10th March 2022 - Kwan, Yuet Ling Linda (PUPIL: International Journal of Teaching, Education and Learning, 2022)
The addition is the first mathematics skill to which most students are introduced. The ability to add numbers gives students a framework for learning mathematics, initially in kindergarten and, subsequently in elementary school. This paper aims to examine the impact exerted by experiential learning on students’ level of academic performance on addition problems. This study arises out of research in a school where students aged between seven and nine, had experienced substantial difficulty in problem-solving in mathematics. The study was designed to discover why such a large body of students had so many difficulties in solving simple arithmetic problems. In the study, 27 students were given a few simple arithmetic problems to determine and comprehend the difficulties that their teachers had indicated their students were having when learning mathematics. The problems involved stories in which a quantity was increased by or combined with a certain quantity to form a total. The quantities involved small natural numbers not exceeding 20. The findings disclosed several problems with learning mathematics. Our results derived that fostering experiential learning strategies favors the students’ understanding of theoretical concepts and leads to the attainment of superior performance